A Synthesis of Six Recent Studies on Numerosity Abilities in an Ant - Cammaerts, Marie-Claire; Cammaerts, Roger (Journal of Biology and Life Science, 2022)
Working on the numerosity ability of the ant Myrmica sabuleti, we have already summarized for the readers’ convenience our previous papers in two successive publications. Since that time, we have produced six more papers on the subject, and we thought it was time to present a summary of them. These studies deal with the ants’ ability in expecting the following element in an arithmetic or a geometric sequence, as well as with the required similarity between visual cues and the maximum horizontal and vertical distance between such cues enabling the ants to mentally add them up. The experimental methods that were used in these studies are here only briefly reported and their most important results are concisely related, as the extended information can be found in these six papers here summarized. We present novel tables and figures for illustrating this synthesis.